Partisipasi Masyarakat dalam Pengembangan Kepariwisataan di Kelurahan Bitung Karangria Manado - Steven Y. Kawatak; Teddy Tandaju; Yelly A. Walansendow; Karyn M. A. Koyongian (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Bitung Karangria Sub-district is located in a strategic location and has great potential for development. Apart from optimal support by the government, the success of tourism development cannot be separated from the active participation of the community. This research aims to see the extent of community participation in Bitung Karangria Sub-district in making local tourism development a success and also to determine the driving and inhibiting factors encountered by the community. The method used is a descriptive qualitative approach, where data is collected through interviews with the government and local communities. The research results show that the community has actively participated through participation in the form of donations of ideas and energy as well as through participation by implementing their skills. It was also found that several factors driving local community participation were the opportunity to improve economic welfare, the existence of psychological support from the government which was willing to listen to input and criticism from the community and the presence of elements of society who had a strong tourism knowledge background. However, there are several factors that hinder community participation, for example the lack of readiness and awareness to participate and the inadequate knowledge and skills of some communities to participate actively.   ABSTRACT Bitung Karangria Sub-district is located in a strategic location and has great potential for development. Apart from optimal support by the government, the success of tourism development cannot be separated from the active participation of the community. This research aims to see the extent of community participation in Bitung Karangria Sub-district in making local tourism development a success and also to determine the driving and inhibiting factors encountered by the community. The method used is a descriptive qualitative approach, where data is collected through interviews with the government and local communities. The research results show that the community has actively participated through participation in the form of donations of ideas and energy as well as through participation by implementing their skills. It was also found that several factors driving local community participation were the opportunity to improve economic welfare, the existence of psychological support from the government which was willing to listen to input and criticism from the community and the presence of elements of society who had a strong tourism knowledge background. However, there are several factors that hinder community participation, for example the lack of readiness and awareness to participate and the inadequate knowledge and skills of some communities to participate actively.